2020
DOI: 10.1111/cod.13710
|View full text |Cite
|
Sign up to set email alerts
|

Suitable test concentration of cobalt and concomitant reactivity to nickel and chromium: A multicentre study from the Swedish Contact Dermatitis Research Group

Abstract: Background In Sweden, cobalt chloride 0.5% has been included in the baseline series since the mid‐1980s. A recent study from Stockholm showed that cobalt chloride 1% petrolatum (pet.) was more suitable than 0.5%. Cobalt chloride at 1.0% has been patch tested for decades in many European countries and around the world. Objectives To study the suitability of patch testing to cobalt 1.0% vs 0.5% and to analyze the co‐occurrence of allergy to cobalt, chromium, and nickel. Results Contact allergy to cobalt was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Lamtai et al showed that in male rats, all doses of Cd triggered depressive-like behavior, whereas in female rats, only those receiving high doses exhibited depressive-like behavior (63). Isaksson et al found a higher percentage of positive skin reactions to Co in females than in males (64). The above results indicated that when we study the association between metal exposure and inflammatory markers, we should not only focus on how different pollutants affect males and females differently but also study the effects at different concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Lamtai et al showed that in male rats, all doses of Cd triggered depressive-like behavior, whereas in female rats, only those receiving high doses exhibited depressive-like behavior (63). Isaksson et al found a higher percentage of positive skin reactions to Co in females than in males (64). The above results indicated that when we study the association between metal exposure and inflammatory markers, we should not only focus on how different pollutants affect males and females differently but also study the effects at different concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Some variation can be a result of regional differences in exposure and patient selection (eg, testing with Compositae mix) 34 . However, it might also be attributed to a lack of calibration of patch testing techniques or differing clinical readings and interpretations of patch tests, especially in the case of 1+, irritant, and doubtful reactions 35‐37 . EpiReg is believed to be a potentially useful tool for education about and calibration of patch testing in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…3 With relation to patient sex, men exhibited a prevalence of 19.8% compared to 18.1% of women, whereas a multicenter study by the Swedish Contact Dermatitis Research Group found a higher proportion of women with positive tests for cobalt 1%. 22 The allergen triethanolamine is an emulsifier in cosmetic products and is widely used in sunscreen and moisturizers in Brazil, where it had a prevalence of 17.3%, being more common among men and in the 25 to 48 years age group. 23 Chrome had a higher prevalence of positive tests among males (16.8%) and the 0 to 12 years age group (28.8%).…”
Section: Tablementioning
confidence: 99%